Contribuições para o estudo da doença do disco intervertebral em cães - Ripplinger, Angel (2021)
Thoracolumbar (TL) intervertebral disc disease (IVDD) is a common cause of neurological dysfunction in dogs. IVDD is a broad term used to refer to a series of diseases that affect the intervertebral disc of dogs, and that may or may not involve degeneration of the disc. Intradural intervertebral disc extrusion (IIVDE) is one of the rare types of IVDD, that can affect the TL spinal cord region of dogs. IIVDE is difficult to diagnose and there are still doubts about treatment. Article 1 of the present thesis presents a case report of IIVDE, whose diagnosis was made during the transoperative period. The changes in myelography were inconclusive and the surgical decision was made based on history, clinical findings and simple radiography. The surgery allowed adequate recovery of the patient and the collection and analysis of the material removed during the surgery allowed the definitive diagnosis of IIVDE. Toracolumbar intervertebral disc extrusion (IVDE) (extradural) is the most common presentation of IVDD in dogs. Dogs with paraplegia without deep pain perception, secondary to IVDE, have questionable prognosis, when they remain without surgical treatment for a long time. The article 2 shows results of the return to ambulation of dogs submitted to surgery to treat TL IVDE, with 96 hours (four days) or more of paraplegia without deep pain perception. The results allow us to affirm that there is a possibility above 45% of return to walking for these dogs when treated surgically. Finally, we can add that IVDD still presents a vast field of clinical studies to better understand the processes involved and to better approach the patient affected by it.